2019 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW) 2019
DOI: 10.1109/eurospw.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

CRC-PUF: A Machine Learning Attack Resistant Lightweight PUF Construction

Abstract: Adversarial machine learning is an emerging threat to security of Machine Learning (ML)-based systems. However, we can potentially use it as a weapon against ML-based attacks. In this paper, we focus on protecting Physical Unclonable Functions (PUFs) against ML-based modeling attacks. PUFs are an important cryptographic primitive for secret key generation and challenge-response authentication. However, none of the existing PUF constructions are both ML attack resistant and sufficiently lightweight to fit low-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The cyclic redundancy check PUF (CRC PUF) design discussed in [12] consists of one n ‐bit LFSR and one n ‐bit arbiter PUF. The total GE for 128‐bit CRC PUF is calculated by considering one 128‐bit LFSR apart from basic 128‐bit arbiter PUF.…”
Section: Simulation and Results Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The cyclic redundancy check PUF (CRC PUF) design discussed in [12] consists of one n ‐bit LFSR and one n ‐bit arbiter PUF. The total GE for 128‐bit CRC PUF is calculated by considering one 128‐bit LFSR apart from basic 128‐bit arbiter PUF.…”
Section: Simulation and Results Analysismentioning
confidence: 99%
“…In other words, the MARPUF is more resistant to ML attacks. We also compared the proposed MARPUF with other PUF schemes like CRC PUF [12], interpose PUF [13] , and Wang et al PUF [16] to evaluate the hardware cost and it is observed from Table 3 that the proposed MARPUF has the edge over the said PUF designs. Furthermore, MARPUF requires two clock cycles to generate the output as PUF response, which is higher than the conventional PUF like RO PUF and arbiter PUF designs, as MARPUF involves two rounds of operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has also surfaced non-invasive ML attack vulnerabilities to strong composite PUF models and lightweight PUF models [35]. Consequently, sound mathematical representations and provable guarantees are studied to theoretically justify the PAC-learnability for a family of PUFs [6], which has further led to the exploratory development in the field of ML-resistant PUF designs [4,14,15,41].…”
mentioning
confidence: 99%